Generic skills needed to produce human capital with "first class mentality". - Gani Hamzah, Mohd Sahandri; Abdullah, Saifuddin Kumar (Eurojournals, 2009)
Generic skills are the general skills, qualities, knowledge, abilities and traits a person should possess to succeed in one’s studies and career. These skills are not specific but are skills which cut horizontally across all industries and vertically across all job from entry level to chief executive officer. It is beginning to be broadly accepted that the contemporary workplace is characterized by continuous change. One impact of the transformation is that lifelong learning has been identified as a means of developing human capital. It is widely believed that such dimensions of performance as learning, innovation and enterprise can be enhanced by placing greater emphasis on generic skills in teaching and learning process. The objectives of the study are to produce human capital with “first class mentality”, identify the generic skills required to produce human capital with ”first class mentality”, incorporate the generic skills in the process of teaching and learning, assess the development of generic skills and discuss the barriers in teaching and learning generic skills. There are several reasons for the current perceived importance of the generic skills, the primary one being employment and industry-driven. To incorporate generic skills in teaching and learn ing, there are two approaches can be implemented that is diffusion model approach and infusion model approach . The other reasons are the need to remain competitive, need to acquire new knowledge in. a knowledge-based world and the need to socialize and interact in an inter-dependent world.